Investigation of the Leadership Behaviors of Sports Faculty Students - Mutlu, Tonguç Osman; Şentürk, Halil Evren; Akoğlu, Halil Erdem; Çetinkaya, Asil; Ağılönü, Ali (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2020)
The study aimed to analyze the leadership behaviors of sports faculty students according to gender, age and class variables and to make suggestions for the development of leadership behaviors of students according to the results of the research. The sample of the study consisted of 499 students (N women = 196; Nerkek = 303) who were selected according to the random sampling method and volunteered for the study. The “Leadership Behaviors Scale", developed by Ekvall and Arvonen (1991) and adapted to Turkish by Tengilimoğlu (2005), was used to determine the leadership behaviors of students participating in the research. The data were analyzed by using SPSS 22 with Mann Whitney U, Kruskall Walliss and Spearman Correlation tests. According to the research findings, it was observed that the sports faculty students have high leadership behavior levels and female students displayed higher levels of leadership behavior in production-oriented leadership behaviors than male students. Besides, it was found that 3 th and 4th class students had higher levels of production and change-oriented leadership behaviors than those who were in their first two years of education. Lastly, older students exhibited higher levels of production and change-oriented leadership behaviors than younger students.